The Impact of Virtual Islamic Learning Spaces on Student Engagement and Academic Performance in Indonesia - Taufik, Herman; Zulkarnaen, Muhammad (The Eastasouth Journal of Learning and Educations, 2025)
This study examines the impact of virtual Islamic learning spaces on student engagement and academic achievement in Indonesia. As digital education becomes increasingly integrated into religious instruction, understanding its effectiveness is essential. A quantitative research method was employed, involving 150 respondents who participated in virtual Islamic learning programs. Data were collected using a Likert-scale questionnaire (1–5) and analyzed using SPSS version 25. The results revealed a significant positive relationship between the use of virtual learning platforms and both student engagement and academic achievement. Multiple linear regression analysis showed that student engagement plays a mediating role, with a stronger influence on academic outcomes compared to direct platform use. These findings highlight the importance of well-structured and interactive virtual Islamic learning environments in enhancing educational outcomes. The study contributes valuable insights for educators, policymakers, and digital content developers aiming to strengthen Islamic education in the digital era.